(untitled) (Journal of Oriental Studies, 2019)
On this article,Al- Faraby is widely considered the problem of education and pedagogy in the philosophical system as the social phenomenon. This phenomenon is closely related to the human body, as well as confirms that each individual can be the member of society, can achieve the level of his own personality, on the result to achieve their main goals prepares from the earliest age. hole activities directed to education on Al-Farabi`s view, formulated on certain stage and values in society, teaching and practical possibilities as the personal development. . The main goal of education to achieve the level of personality, but the main goals of people living in this world absolute goodnesss- defined as achieving the highest level of happiness.. On theseexplanations edited the importance of scientific works of ancientauthors,repaired and explained,formed to the methodical type as most pupil will be able to read and understand. Al-Farabi united the learning and experience as the importance of education: every theoretical knowledge must be practiced in practice. Key words: Education, theory, experience, political leader, moral, an individual, pedagogical, intellectual knowledge, didactics.